Implication of potassium on the quality of cherry tomato fruits after postharvest during cold storage. (March 2014) - Constán-Aguilar, Christian; Leyva, Rocio; Romero, Luis; Soriano, Teresa; Ruiz, Juan Manuel
Abstract The influence of the potassium (K) content in tomato fruits over compounds or antioxidant characteristics during the postharvest period in cold storage is little known. The aim of this work was to determine whether the effect of a biofortification programme with K in KCl form can improve the postharvest storage of cherry tomato fruits at 4 °C. K treatments applied during the crop cycle of the plants: 5, 10 and 15 mM of KCl. Biomass parameters, levels of K, antioxidant capacity test, Vitamin C, carotenoids, phenolic compounds and free polyamines in tomato cherry fruits were measured. Our results show that the treatment with 15 mM KCl prevents weight and water loss during postharvest storage at 4 °C, increases K concentration, and bolsters the antioxidant capacity, since the concentration in lycopenes as well as flavonoids and derivatives rose, while the contents in Vitamin C together with hydroxycinnamic acids and derivatives remained stable.